Health-seeking behaviour of stroke patients in a rural area of Bangladesh - Alam, Md Badrul; Saha, Uttam Kumar; Mashreky, Saidur Rahman; Hussain, AHM Enayet; Haque, Md Atiqul; Rahman, AKM Fazlur; Dalal, Koustuv; Mohammad, Quazi Deen (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Improper health-seeking behaviours (HSB) have been correlated with detrimental health outcomes, elevated rates of illness and mortality. The study aimed to investigate how stroke patients in a rural community of Bangladesh seek health care. Methods: A cross-sectional survey was conducted in the Raiganj sub-district of Sirajganj district from January to June 2016, using a validated screening tool to identify stroke patients at the household level. Neurologists confirmed the diagnosis after examining all suspected cases. Out of the 419 suspected cases identified during the screening process, 186 cases were officially reported after undergoing a confirmed diagnosis. Information on health-seeking behaviour was collected through face-to-face interviews with patients or their attendants. Results: After experiencing a stroke, approximately 35% of patients received treatment from unregistered care providers and over 40% received treatment outside of a hospital setting. Males were significantly more likely than females to receive treatment from registered physicians or hospitals (P<.05 and P<.01). A significantly higher proportion of educated individuals sought healthcare from registered physicians or hospitals (P<.05). Although better health-seeking behaviour was observed among higher-income groups, the findings were not statistically significant. Around 67% of patients were found to be hypertensive, with about one-third of them not taking any medication for their elevated blood pressure. Approximately 37% of patients had elevated blood glucose levels but only 22% were taking medication. Conclusion: A notable proportion of stroke patients in rural Bangladesh sought treatment from unqualified service providers. Health-seeking behaviour was associated with factors such as gender, education, and economic condition.